1996
DOI: 10.1099/0022-1317-77-3-547
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus replication alters hormone-regulated host development

Abstract: The baculovirus Lymantria dispar nuclear polyhedrosis virus interferes with insect larval development by altering the host's hormonal system. The level of haemolymph ecdysteroids, the insect moulting hormone, was found to be higher in virus-infected larvae than in uninfected controls. This was consistently observed in both fourth instars and day 5-infected fifth instars. The rate of hormone synthesis was examined by in vitro incubation of the prothoracic gland. Gland activity in virus-infected larvae was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…This indicated that the ability of the PGs to produce and release ecdysteroids was not significantly altered by MySEV infection, rather the lower haemolymph ecdysteroid levels appeared to result from the lack of ecdysteroid induction by PTTH. A similar suppression of ecdysteroid release is observed in larval Lymantria dispar infected with Lymantria dispar nucleopolyhedrovirus (LdNPV) (Park et al, 1996). The authors of this study speculated that the release of PTTH from the brain is blocked because of the lack of available PTTH to stimulate PGs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This indicated that the ability of the PGs to produce and release ecdysteroids was not significantly altered by MySEV infection, rather the lower haemolymph ecdysteroid levels appeared to result from the lack of ecdysteroid induction by PTTH. A similar suppression of ecdysteroid release is observed in larval Lymantria dispar infected with Lymantria dispar nucleopolyhedrovirus (LdNPV) (Park et al, 1996). The authors of this study speculated that the release of PTTH from the brain is blocked because of the lack of available PTTH to stimulate PGs.…”
Section: Discussionmentioning
confidence: 52%
“…This lack of increase was attributed to a reduction in the synthesis and secretion of PTTH from the brain following parasitization. Similarly, a reduction in ecdysteroid titre is observed in final instar caterpillars that are infected with EPVs such as CFEV (Palli et al, 2000) and AHEV (Nakai et al, 2004), and the baculovirus LdNPV (Park et al, 1996). Furthermore, Sakurai & Imokawa (1988) have shown that elevated JH titre in the haemolymph prevents the release of PTTH.…”
Section: Discussionmentioning
confidence: 95%
“…We then held these infected larvae at 28°C for 5 days, before placing them on foliage in the field. Because infected neonates do not molt to the second instar (Park et al 1996), it was possible to identify and discard the small number of larvae that did not become infected. Because our emphasis was on estimating the decay rate rather than heterogeneity in infection risk, we reduced heterogeneity by using larvae from a USDA colony that has been reared in the laboratory for decades (Dwyer et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…This is the case of some insects viruses, for example, the baculovirus group has a higher pathogenicity in the larval and juvenile stages than in adults (Evans and Shapiro, 1997) and Lymantria dispar nuclear polyhedrosis caused by a baculovirus interferes with the larval development (Park et al, 1996). Concerning about shrimp, baculoviral mid-gut gland necrosis virus (BMNV) affects exclusively larval stages of P. japonicus (Momoyama and Sano, 1989).…”
mentioning
confidence: 99%